Polypharmacological Properties and Therapeutic Potential of β-Caryophyllene: A Dietary Phytocannabinoid of Pharmaceutical Promise - Sharma, Charu; M. Al Kaabi, Juma; M. Nurulain, Syed; N. Goyal, Sameer; Amjad Kamal, Mohammad; Ojha, Shreesh (Current Pharmaceutical Design, 2016)
Background: β-Caryophyllene (BCP) is a natural bicyclic sesquiterpene abundantly found in essential oils from various spices, fruits and medicinal as well as ornamental plants. It is approved by United States Food and Drug Administration and European agencies as food additive, taste enhancer and flavoring agent and termed as a phytocannabinoid. Methods: All the available literature on BCP and its synonyms were collected through different literature databases. Results: BCP was found to elicit a full agonist action on cannabinoid type 2 (CB2) receptors, a G-protein coupled receptor representing important therapeutic target in several diseases. Activation of CB2 receptors notably appeared devoid of psychotropic adverse effect of cannabinoids contrary to the CB1 receptors. In addition, it activates peroxisome proliferated activator receptors (PPARs) isoforms; PPAR-α &-γ and inhibits pathways triggered by the activation of toll like receptor complex; CD14/TLR4/MD2, reduce immuneinflammatory processes and exhibit synergy with μ-opioid receptor dependent pathways. Additionally, it found as potent antagonist of homomeric nicotinic acetylcholine receptors (α7-nAChRs) and devoid of effects mediated by serotonergic and GABAergic receptors. It also modulates numerous molecular targets by altering their gene expression, signaling pathways or through direct interaction. Various pharmacological activities such as cardioprotective, hepatoprotective, gastroprotective, neuroprotective, nephroprotective, antioxidant, anti-inflammatory, antimicrobial and immune-modulator have been reported in experimental studies. It has shown potent therapeutic promise in neuropathic pain, neurodegenerative and metabolic diseases. Conclusion: The present review provides a comprehensive insight of pharmacological and therapeutic potential of BCP, its molecular mechanism and signaling pathways in different pathological conditions. The review also examines the possibility of its further development as a novel candidate for various pathologies considering the polypharmacological and multifaceted therapeutic properties potential along with favorable oral bioavailability, lipophilicity and physicochemical properties.
Keywords: trans-Caryophyllene